The Spatiotemporal Pattern of Cultural Evolution Response to Agricultural Development and Climate Change From Yangshao Culture to Bronze Age in the Yellow River Basin and Surrounding Regions, North China - Wang, Lin; Cui, Yifu (Frontiers in Earth Science, 2021)
The processes and mechanisms of cultural evolution provide helpful insight into the origin and development of civilizations. This paper analyses data from the national archaeological survey using kernel density analysis, a geospatial tool provided by ArcGIS10 software, to explore the spatiotemporal pattern of cultural evolution from the beginning of the Yangshao cultural period to the Bronze Age in the Yellow River basin. Agricultural development and the environmental background of this region were reconstructed using published flotation materials and high-resolution paleoclimate records. The results indicate that cultural expansion and differentiation from Yangshao (7000-5000 BP) to Longshan period (4600-4000 BP) are responding to the establishment and strengthen of millet-based agriculture, and the appearance of multiple subsistence strategy in the context of environmental deterioration. To Bronze Age, the center of sites accumulates to the Central Plain and Shandong, in contrast to the continuous cultural expansion and differentiation. The opposite circumstance may result from early urbanization along with the formation of social system with high centralization of power.